PENGARUH DIFERENSIASI BUDAYA TERHADAP INTERAKSI SOSIAL MTS AGAMA ISLAM MERTAPADA KULON KABUPATEN CIREBON - Ningsih, Sri Wahyu; Mulyana, Asep; Wijaya, Apriyanda Kusuma (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The purpose of this study was "To find out whether there is an influence of cultural differentiation on the social interactions of class IX students of Islamic Islamic Junior High School Mertapada Kulon". This study uses quantitative research methods using the type of research used causal comparative (Ex Post Facto), suggesting that the study was conducted before the differences in the independent variables due to the natural development of events. 50 samples, data obtained using research instruments in the form of questionnaires distributed to students and analyzed statistically or quantitatively. The results of this study show the number of Likert scale calculations getting results 0% strongly agree (STS), 1% disagree (TS), 8% doubtful (RR), 47% agree (S), and 44% strongly agree (SS). ) in the Likert scale percentage, which is sufficient because the average score of 4.17 (41%) is in the range of 40% "“ 59.99% = Enough. Based on the T test for the cultural differentiation variable (X) on the social interaction variable (Y) it shows a significance value of 0.00 which is smaller than 0.05 (0.00 0.05) and the t-count value is greater than ttable (11,414 2.021). So the decision taken is that Ho is rejected and Ha is accepted, that there is a significant influence of cultural differentiation. The test that has been carried out by researchers has an R Square value of p.731, this explains that the influence of the variable (Cultural Differentiation) on Y (Social Interaction) is 73.1% and based on 27.0% is explained by other factors other than the independent variable